A STUDY ON THE PARTICIPATION OF GIRL ATHLETES IN THE STATE OF ANDHRA PRADESH DURING THE YEARS 2002 TO 2008 - BhavaniRajeshwari, S. (The journal of contemporary issues in business and government, 2009)
The word athletics is derived from the Greek word "athlos―, meaning "contest" or "task.‖Athletics is an exclusive collection of sporting events that involve competitive running, jumping, throwing, and walking. The most common types of athletics competitions are track and field, road running, cross country running, and race walking.Track and field is one of the oldest of sports.The simplicity of the competitions, and the lack of a need for expensive equipment, makes athletics one of the most commonly competed sports in the world.Track and Field as a modern sport started in England during the 19th century.